Detection of feline panleukopenia with antigen test kit - Priambudi, M. Zuliono Dwi Risky; Haskito, Ajeng Erika Prihastuti; Inayah, Khoirul; Adrenalin, Sruti Listra (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2022)
Feline panleukopenia is an infectious disease caused by the feline panleukopenia virus (FPV). The signs of infected cats in-clude fever, lethargy, anorexia, diarrhoea, and vomit. A secondary infection can exacerbate this condition, such as bacteria. The aim of this study to find out the diagnostic technique and the FPV detection method using the FPV antigen test kit. On August 2nd, 2021, the cat was brought to Griya Fauna Mojokerto with severe flu. In addition, based on the information, the cat has decreased appetite. The physical examination results that the temperature was 39.5 °C, bodyweight of 2.9 kg, and the cat looked weak when observed. Further, the FPV antigen test kit was used to confirm the diagnosis in this case. The FPV antigen test kit showed positive results that indicated by forming two lines on the test line (T) and the control line (C).